Dysfunction in macula, retinal pigment epithelium and post retinal pathway in acute organophosphorus poisoning. (1st February 2021) - Dahanayake, Padmini; Dassanayake, Tharaka L.; Pathirage, Manoji; Colombage, Anuradha; Gawarammana, Indika B.; Senanayake, Saman; Sedgwick, Michael; Weerasinghe, Vajira S.
Abstract: Context: Organophosphorus (OP) insecticide poisoning is a significant health problem in South Asian countries. Although cholinergic receptors are present at the junction between photoreceptors and the retinal pigment epithelium (RPE), human studies of the effects of OP poisoning on the visual pathways are very few. This study aims to demonstrate the pattern of changes in retina and post retinal pathways in patients with acute OP poisoning using visual electrophysiological tests. Methods: This is an observational, cross-sectional study conducted at the Neurophysiology Unit, Teaching Hospital, Peradeniya, Sri Lanka. We tested 16 patients recovered from cholinergic phase, at least 24 h after deatropinization and within 8 weeks of OP ingestion. We assessed the functional integrity of the photoreceptors and ganglion cells of the macula by pattern electroretinography (PERG); RPE by electro-oculography (EOG); and post retinal pathways by pattern reversal visual evoked potentials (PR-VEP). Latencies and amplitudes of PR-VEP and PERG, light peak (LP), dark trough (DT) and Arden ratio of EOG were determined in patients and compared with 16 controls using the Mann–Whitney U test. Results: Of the 16 OP-poisoned patients (median age of 37 ± IQR 20 years), six (37.5%) had reduced Arden ratio with reference to the International Society of Clinical Electrophysiology of Vision cut-off value of 1.7. The median Arden ratio in patients (1.69 ± IQR 0.36) was significantly lower compared to controls (1.90 ± IQR 0.4). The median latencies and amplitudes of PR-VEP or PERG were not significantly different between patients and controls. However, three patients had prolonged P100 latencies in PR-VEP and one had prolonged P50 latency in PERG. Conclusions: Acute OP poisoning seems to affect the functions of the RPE and the visual electrophysiological changes outlast the cholinergic phase. Limited evidence suggests that photoreceptors of the macula region and post retinal pathway might be affected in some patients.